Production Performance, Reproduction and Immunity of Sentul Hens at Different IgY Concentrations - Melly Pratiwi Setyawati; Niken Ulupi; Sri Murtini; Cece Sumantri (Buletin Peternakan, 2019)
The aim of this study was to evaluate the effect of different IgY concentrations on the production, reproduction and immunity of Sentul chicken. This research used 20 month-old Sentul chickens which consisting of 10 chickens with high IgY concentration and 10 chickens with low IgY concentration Parameters observed included prelayer performance (feed consumption, weight gain, feed conversion, morbidity and mortality), layer performance (feed consumption, egg production, egg weight, feed conversion, hatchability, morbidity and mortality), and immunity at chicks (IgY concentration of eggs and chicks serum). The experiment was conducted as a completely randomized design. The treatments were high and low IgY concentration. All treatments were repeated 10 times. The data obtained were analyzed using the SAS program t-test. Morbidity and mortality were analyzed descriptively. The results of this research indicated that the prelayer period, chickens with high IgY concentration had a higher performance than chicken with low IgY concentration. This is caused by about 30% chickens with low IgY were in sick condition for approximately seven days. Further, the layer period showed that the chickens with high IgY concentration had lower production performance than the chicken with low IgY concentration. The study concluded that chickens at low IgY concentrations are susceptible to exposure to antigens that lead to decreased productivity. In normal conditions hens, Sentul with high IgY concentration resulted in low production. The observation of chicken immunity showed that concentration of IgY from chicks and eggs did not differ between hens with high IgY concentrations and hens with low IgY concentrations.